Pembuatan RPG Horror Survival Game Sejarah Pahlawan Nasional Indonesia Menggunakan Unity Dan C# - Kharisma Saga Lyrananda; Nenna Irsa Syahputri; Khairunnisa (SNASTIKOM, 2022)
One of the popular entertainments carried out by young people in today's era is video games, which is video gamehas an educational nature or is just entertainment, usually a video game only focuses on the storyline andmechanics of the game. Many times we find video games that come from foreign products where they incorporateelements of behavior and culture from their country into the game storyline that can result in players in Indonesiagetting to know foreign cultures better than their own cultures. The game that I want to create is a role playingfirst person game that is very interactive and has a tense storyline, accompanied by having a simple educationthat makes the players understand the knowledge of the history of Indonesian Heroes, such as remembering theyear on an event that can continue the storyline, and develop the player's instincts about what kind of strategy canwin this game. Basically, the animation processing in this game uses various programs including: Unity 3D, orUnreal Engine, assisted by supporting applications such as Blender for making 3D models and using the C#programming language. The result of the game created is in the form of a .exe file which will later be compatiblewith a Personal Computer (PC) device. Based on the results of tests that have been carried out, this educationalmedia is enough to help the introduction of the history of Indonesian Heroes, and also creates a tense atmospherein the process of playing